Preclinical characterization of a novel investigational monoclonal antibody CM313 with potent CD38-positive cell killing activity - Liu, Wei; Yu, Juntao; Sun, Kaiwen; Song, Qin; Li, Yuling; He, Yanyun; Wang, Yanrong; Xu, Gang; Wang, Changyu; Chen, Bo (Frontiers in Immunology, 2024)
Introduction CM313 is currently under clinical investigation for treatments of multiple myeloma, systemic lupus erythematosus, and immune thrombocytopenia. We aimed to report the preclinical profile of the novel therapeutic anti-CD38 monoclonal antibody (mAb) CM313, with an emphasis on the difference with other CD38-targeting mAb. Methods The binding of CM313 to CD38 recombinant protein across species was assessed using ELISA. The binding of CM313 to CD38-positive (CD38+) cells was detected using flow cytometry assays. CM313-induced complement-dependent cytotoxicity (CDC), antibody-dependent cellular cytotoxicity (ADCC), antibody-dependent cellular phagocytosis (ADCP) and apoptosis on different CD38+ cells were assessed by LDH release assays or flow cytometry assays. The effect of CM313 on CD38 enzymatic activity was measured using fluorescence spectroscopy. CM313 immunotoxicity in human blood was assessed using flow cytometry assays, ELISA, and LDH release assays. Anti-tumor activity of CM313 was assessed in multiple mouse xenograft models. Safety profile of CM313 were evaluated in cynomolgus monkeys and human CD38 transgenic (B-hCD38) mice. Results There exist unique sequences at complementarity-determining regions (CDR) of CM313, which facilitates its affinity to CD38 is consistently higher across a spectrum of CD38+ cell lines than daratumumab. In vitro studies showed that CM313 induces comparable killing activity than daratumumab, including ADCC, CDC, ADCP, apoptosis induced by Fc-mediated cross-linking, and effectively inhibited the enzymatic activity of CD38. However, CM313 showed more potent CDC than isatuximab. In vivo, CM313 dose-dependently inhibited xenograft tumor growth, both as a monotherapy and in combination with dexamethasone or lenalidomide. Furthermore, CM313 was well tolerated with no drug-related clinical signs or off-target risks, as evidenced by 4-week repeat-dose toxicology studies in cynomolgus monkeys and B-hCD38 mice, with the later study showing no observed adverse effect level (NOAEL) of 300mg/kg once weekly. Discussion CM313 is a novel investigational humanized mAb with a distinct CDR sequence, showing comparable killing effects with daratumumab and stronger CDC activity than isatuximab, which supports its clinical development.